(3a+5)(2a-9)=0

Simple and best practice solution for (3a+5)(2a-9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3a+5)(2a-9)=0 equation:


Simplifying
(3a + 5)(2a + -9) = 0

Reorder the terms:
(5 + 3a)(2a + -9) = 0

Reorder the terms:
(5 + 3a)(-9 + 2a) = 0

Multiply (5 + 3a) * (-9 + 2a)
(5(-9 + 2a) + 3a * (-9 + 2a)) = 0
((-9 * 5 + 2a * 5) + 3a * (-9 + 2a)) = 0
((-45 + 10a) + 3a * (-9 + 2a)) = 0
(-45 + 10a + (-9 * 3a + 2a * 3a)) = 0
(-45 + 10a + (-27a + 6a2)) = 0

Combine like terms: 10a + -27a = -17a
(-45 + -17a + 6a2) = 0

Solving
-45 + -17a + 6a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(-5 + -3a)(9 + -2a) = 0

Subproblem 1

Set the factor '(-5 + -3a)' equal to zero and attempt to solve: Simplifying -5 + -3a = 0 Solving -5 + -3a = 0 Move all terms containing a to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3a = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3a = 0 + 5 -3a = 0 + 5 Combine like terms: 0 + 5 = 5 -3a = 5 Divide each side by '-3'. a = -1.666666667 Simplifying a = -1.666666667

Subproblem 2

Set the factor '(9 + -2a)' equal to zero and attempt to solve: Simplifying 9 + -2a = 0 Solving 9 + -2a = 0 Move all terms containing a to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2a = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2a = 0 + -9 -2a = 0 + -9 Combine like terms: 0 + -9 = -9 -2a = -9 Divide each side by '-2'. a = 4.5 Simplifying a = 4.5

Solution

a = {-1.666666667, 4.5}

See similar equations:

| 4s+2j=63 | | 4(n-6)-(5-7n)=10n | | 3*-9+2y=-15 | | F(-2)=17-(-2) | | 2j+4s=64 | | 6=-18b | | -3|2-5/4x|=18 | | 5.6=3.8-x/3 | | Y/0.6=2.4 | | 18-2-2w=4-4w | | -4-1=2x-7 | | -10m+3(8+8m)=-6(m-4) | | 2.9*y=5.8 | | 3x(10x2)/5 | | 10x+3(x-15)= | | 7/9÷5/9 | | 2x-3x-6=2x+1 | | 16/5m^2-81/5p^2 | | 4(2x-9)=8(x-4) | | 17xyz+11xyz-21xyz-5xyz= | | x=25000 | | (15x-2)+(7x+4)=180 | | 4w^2+56=0 | | ad=0.45d+180 | | -86+2x=-9x+189 | | -36-x=69+6x | | -135-7x=39-x | | 3z+19=173 | | 5x-15+3x+6=7x | | -83+x=-9x+97 | | -17-x=31+2x | | 2*y=5.8 |

Equations solver categories